Experimental transmission of Pasteurella multocida 6:B in goats - Shamsuddin, Mohd Shafarin; Saad, Mohd Zamri; S. M., M. Jamil; Bejo, Siti Khairani; Saharee, Abdul Aziz (Cabi, 2007)
Haemorrhagic septicaemia (HS) is an acute disease of cattle and buffaloes caused by Pasteurella multocida 6:B. Outbreaks of the disease have been closely associated with carrier animals that transmit the organism to susceptible animals during stressful condition. This study was conducted to determine whether goats exposed intranasally to P. multocida 6:B can transmit the organism to contact goats. Thirty-six healthy local Katjang goats were divided into four groups and goats of groups 1 and 3 were each inoculated intranasally with a 1-ml inoculum that contained 1x109 CFU/ml of live P. multocida 6:B. Following the exposure, all goats of groups 3 and 4 were injected with dexamethasone at the rate of 1 mg/kg for three consecutive days. At the end of the dexamethasone treatment, goats of groups 1 and 2 were commingled but kept separate from goats of groups 3 and 4, which were commingled in another pen. Three surviving goats from each group were killed on days 7, 14 and 21 post-exposure for postmortem examination. Naso-pharyngeal mucus and heart blood were collected on swabs. Tissues from lungs, lymph nodes and tonsils were collected for bacteriological isolation and identification. Only one goat of group 3 died 6 days post-exposure showing clinical signs and lesions typical of HS. Other goats showed mild signs of upper respiratory tract infection. Goats of all groups developed acute mild pneumonic lesions, however, those treated with dexamethasone had significantly (P<0.05) more extensive lesion scoring based on the lesion scoring system. P. multocida 6:B was isolated from the nasal mucosa and lung lesions of exposed and contact goats not treated with dexamethasone. Exposed and contact goats treated with dexamethasone carried the organism for 21 days. P. multocida isolation from heart blood was made only from exposed and contact goats treated with dexamethasone. P. multocida was isolated from the lymph node of the goat that died during the experiment.